Mechanical Ventilation in Pediatric and Neonatal Patients - Kollisch-Singule, Michaela; Ramcharran, Harry; Satalin, Joshua; Blair, Sarah; Gatto, Louis A.; Andrews, Penny L.; Habashi, Nader M.; Nieman, Gary F.; Bougatef, Adel (Frontiers in Physiology, 2022)
Pediatric acute respiratory distress syndrome (PARDS) remains a significant cause of morbidity and mortality, with mortality rates as high as 50% in children with severe PARDS.1 Despite this, pediatric lung injury and mechanical ventilation has been poorly studied, with the majority of investigations being observational or retrospective and with only a few randomized controlled trials to guide intensivists.2 The most recent and universally accepted guidelines for pediatric lung injury are based on consensus opinion rather than objective data.3 Therefore, most neonatal and pediatric mechanical ventilation practices have been arbitrarily adapted from adult protocols, neglecting the differences in lung pathophysiology, response to injury, and co-morbidities among the three groups. Low tidal volume ventilation has been generally accepted for pediatric patients,4 even in the absence of supporting evidence.5 No target tidal volume range has consistently been associated with outcomes,6 and compliance with delivering specific tidal volume ranges has been poor.7 Similarly, optimal PEEP has not been well-studied, with a general acceptance of higher levels of FiO2 and less aggressive PEEP titration as compared with adults.8 Other modes of ventilation including airway pressure release ventilation and high frequency ventilation have not been studied in a systematic fashion and there is too little evidence to recommend supporting or refraining from their use.3 There have been no consistent outcomes among studies in determining optimal modes or methods of setting them. In this review, the studies performed to date on mechanical ventilation strategies in neonatal and pediatric populations will be analyzed. There may not be a single optimal mechanical ventilation approach, where the best method may simply be one that allows for a personalized approach with settings adapted to the individual patient and disease pathophysiology. The challenges and barriers to conducting well-powered and robust multi-institutional studies will also be addressed, as well as reconsidering outcome measures and study design.